• Matéria: Matemática
  • Autor: mabson12
  • Perguntado 8 anos atrás

simplifique a expressao (343)^-2/3.

Respostas

respondido por: Diogolov
51
343^{\frac{-2}{3}}=\\\\
{(\dfrac{1}{343})}^{\frac{2}{3}}=\\\\
{(\dfrac{1}{343^2})}^{\frac{1}{3}}=\\\\
{(\dfrac{1}{117649})}^{\frac{1}{3}}=\\\\
 \sqrt[3]{\dfrac{1}{117649}}=\\\\
\dfrac{1}{49}
respondido por: rafanascentes2016
6

343

3

−2

=

(

343

1

)

3

2

=

(

343

2

1

)

3

1

=

(

117649

1

)

3

1

=

3

117649

1

=

49

1

Perguntas similares